6b+4b=-12+8b

Simple and best practice solution for 6b+4b=-12+8b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6b+4b=-12+8b equation:


Simplifying
6b + 4b = -12 + 8b

Combine like terms: 6b + 4b = 10b
10b = -12 + 8b

Solving
10b = -12 + 8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-8b' to each side of the equation.
10b + -8b = -12 + 8b + -8b

Combine like terms: 10b + -8b = 2b
2b = -12 + 8b + -8b

Combine like terms: 8b + -8b = 0
2b = -12 + 0
2b = -12

Divide each side by '2'.
b = -6

Simplifying
b = -6

See similar equations:

| 25*7+11*3+2*3= | | 2x^2+-8x-384=0 | | 2(x+2)=-2(x+6) | | 44=x(5+6) | | 7x-(2x+5)=36 | | 2w-36=w-12 | | 46*7+87*3+21*3= | | W-12=2w-36 | | 1/3✖️3/4 | | 1/3✖️3/4=3/8 | | 29*7+16*3+8*3= | | 6y-14=9y-5 | | -3(y+2)=7y-8+4(2y+4) | | .027+2-.035x=0 | | 540*10+160*3= | | 3s-36=5s-88 | | .027+2=.035x | | -4x+10y=12 | | 15.5-7.9= | | .66(-12c+6)-7c+2c-6= | | 4m-6/5=-3 | | 16.1+6.1= | | -17+2=2x-2x-3x | | b-.25=3.5 | | 16.1-22= | | 3/8-x/4=1/16 | | 12(3x+6)(x-2)=0 | | 3y-76=-40 | | -1y-4y+8y=-6+6 | | -(d-2)= | | (X^2+36)+x^2=3600 | | 3q-17=q-1 |

Equations solver categories